1999
DOI: 10.1021/la990089q
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Relaxation Kinetics of Albumin and Fibrinogen on Hydrophobic Surfaces:  Single-Species and Competitive Behavior

Abstract: We report the kinetic behavior of albumin and fibrinogen adsorption and relaxation from gentle shearing flow and phosphate buffer onto C16 self-assembled monolayers. The adsorption kinetics were generally transport-limited; however, the ultimate coverages depended on the rates at which protein molecules arrived at the surface, suggesting that interfacial relaxations determined the ultimate coverage. Of particular note was a dependence of the ultimate coverage of both proteins on the wall shear rate, in additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

28
268
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(297 citation statements)
references
References 60 publications
28
268
1
Order By: Relevance
“…Protein denaturation on the surface would result in shrinkage of the protein-adsorbed film through the unraveling and flattening of the protein to the surface. Denaturation of surface bound protein can also result in desorption of proteins adjacent to the denaturing protein (27). The specific orientation of BSA on surfaces and the extent of protein denaturation were indeterminate within these experiments, and we shall limit our discussions to more general statements of protein adsorption with regard to adsorbed film thickness.…”
Section: Bsa Adsorption On Sam Coated Siliconmentioning
confidence: 98%
See 2 more Smart Citations
“…Protein denaturation on the surface would result in shrinkage of the protein-adsorbed film through the unraveling and flattening of the protein to the surface. Denaturation of surface bound protein can also result in desorption of proteins adjacent to the denaturing protein (27). The specific orientation of BSA on surfaces and the extent of protein denaturation were indeterminate within these experiments, and we shall limit our discussions to more general statements of protein adsorption with regard to adsorbed film thickness.…”
Section: Bsa Adsorption On Sam Coated Siliconmentioning
confidence: 98%
“…The concentration of BSA is similar to the concentration of proteins in cell culture sera (~6 mg/mL), which in turn is near physiological protein concentrations (~40 mg/mL). Protein adhesion studies found in the literature (23,24,26,27,29) have typically used concentrations between 1.0 -0.01 mg/mL, which is the concentration range where the protein-surface adsorption isotherm rise is steepest. By employing concentrations at which the adsorption isotherm has the steepest slope, the effect of surface passivation is more distinct.…”
Section: Bsa Adsorption On Sam Coated Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers also have used a variety of informative techniques [7,8] to perform kinetic measurements of adsorbed protein as a function of time and equilibrium adsorption isotherms. Wertz et al [9] used total internal reflectance fluorescence (TIRF) to infer the orientation and spreading behavior of fibrinogen and lysozyme on hydrophobic and hydrophilic surfaces from kinetic measurements. Schunack et al [10] observed three different conformations of the molecule on the flat surface terraces at low temperature by STM.…”
Section: Introductionmentioning
confidence: 99%
“…Such limitations can lead to misinterpretations of apparent interfacial phenomena, which are used to explain the biocompatibility of biomaterials. For example, conventional biophysical methods often find that the average surface protein conformation relaxes from native-like to nonnative-like upon surface adsorption, which is interpreted as evidence for unfolding (11)(12)(13)(14). However, the time scales over which these conformational changes reportedly occur are orders of magnitude longer than typical surface residence times of isolated proteins (15), suggesting that the picture of surfaceinduced spreading may be oversimplified.…”
mentioning
confidence: 99%